Working conditions, work outcomes, and policy in Asian developing countries - Raymond Robertson; Hongyang Di; Drusilla Brown; Rajeev Dehejia (Asian Development Bank (ADB), 2016)
Developing country labor practices and the working conditions that result from them are both generally poor and increasingly drawing attention from governments, corporations, and the popular media. This review provides an introduction to some of the leading academic literature and ideas that are important for understanding the persistence of poor labor practices and possible policies to address these conditions. The literature is reviewed with the goal of moving from the root causes of poor conditions to innovative solutions. Several such solutions, such as the Better Work program, are discussed.
Keywords: F66; J8; 330; apparel; personnel economics; working conditions